1981
DOI: 10.1128/mcb.1.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Bromodeoxyuridine mutagenesis in mammalian cells is related to deoxyribonucleotide pool imbalance.

Abstract: The relationship between bromodeoxyuridine (BrdUrd) mutagenesis in mammalian cells and the effects of BrdUrd on deoxyribonucleoside triphosphate pools was analyzed. It was found that the exposure of Syrian hamster melanoma cells to mutagenic concentrations of BrdUrd resulted in the formation of a large bromodeoxyuridine triphosphate (BrdUTP) pool, which remained at a high level for several days. In contrast, the size of the deoxycytidine triphosphate (dCTP) pool dropped rapidly after the addition of BrdUrd, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…The increased mutation frequency induced by increasing BrdUrd concentration correlated with an increase in the ratio of BrdUTP to dCTP (Table 1). This increase was caused by an increase in the size of the BrdUTP pools with increasing BrdUrd concentration, as well as a decrease in the dCTP pool, confirming previous findings (2).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The increased mutation frequency induced by increasing BrdUrd concentration correlated with an increase in the ratio of BrdUTP to dCTP (Table 1). This increase was caused by an increase in the size of the BrdUTP pools with increasing BrdUrd concentration, as well as a decrease in the dCTP pool, confirming previous findings (2).…”
Section: Resultssupporting
confidence: 80%
“…This and other studies (2,7,8,14) provided evidence that BrdUrd mutagenesis in mammalian cells was driven by an increase in the intracellular ratio of BrdUTP to dCTP and occurred only during incorporation of BrdUTP into DNA and that mutations due to replication of BrUra residues in DNA did not occur. (We refer to this mutagenesis as "pool-dependent'" because it is dependent upon the BrdUTP pool levels and not the level of BrUra incorporated into DNA.…”
mentioning
confidence: 92%
“…Recent studies revealed the nucleotide pool imbalance can have severe consequences on DNA metabolism and it is critical in SCE formation. The modulation of SCE by DNA precursors raises the possibility that DNA changes are responsible for the induction of SCE and mutations in mammalian cells (Popescu, 1999;Ashman & Davidson, 1981). While increased levels of CA have been associated with increased cancer risk (Hagmar et al, 1994(Hagmar et al, , 1998, a similar conclusion has not been reached for SCE or MN.…”
Section: Cytogenetic Methods For Detection Of Pesticide Genotoxicitymentioning
confidence: 73%
“…The first step in mutagenesis by dT (or by the dT analog 5-bromodeoxyuridine) apparently is the inhibition of the ribonucleotide reductase-catalyzed reduction of CDP to dCDP, leading to an increase in the intracellular dTTP/dCTP ratio. Subsequently, dTTP, now the nucleotide in excess relative to dCTP, mispairs with template guanine, leading to a GC3AT transition at the next round of replication (2,14,22). We have shown that such mutagenesis by dT (or 5-bromodeoxyuridine) exhibits strong sequence specificity in that it occurs preferentially at the 3Ј G of runs of two or more adjacent G residues, resulting in GC3AT transitions at this position in the multiple guanine run (11,16,17,33).…”
mentioning
confidence: 99%